Assessment of Radio Communication Approaches for the Effective Dissemination of Livestock Production Technologies - Wamatu, Jane; Zeleke, Muluken; Mebratie, Anagaw; Ephrem, Nahom; Abiso, Tesfaye; Belayneh, Tesfa; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2023)
A key factor hindering the advancement of agricultural productivity among smallholder farmers in Sub-Saharan Africa is inadequate agricultural technologies that address specific local problems. The modalities employed for technology transfer often overlook the unique local contexts and the specific needs of the intended recipients. This study investigates various approaches that can be used to effectively disseminate livestock production technologies through radio received by smallholder farmers.